Kriminalisasi Pekerja Seks dalam Pusaran Sistem Hukum Pidana (Studi Kasus Putusan PN Yogyakarta) - Anisah, Laili Nur (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
One of the oldest professions in the world, which has the ambivalence of being needed and criticized by society, is being a sex worker. Many local areas have been closed by the government, but prostitution still exists and continues to increase. The government does not specifically regulate the punishment of sex workers in Indonesia, this raises the question of how sex workers are viewed in Indonesian criminal law. The existence of loopholes in statutory regulations creates legal uncertainty. This has an impact on the implementation of the article by law enforcement officials which can lead to the criminalization of acts that are not criminal. This research uses a normative juridical method, namely research by looking for articles that regulate sex workers and analyzing the implementation of these articles in District Court Decisions. The conclusion from this research is that there are no regulations either in the Criminal Code or outside the Criminal Code that can be used to ensnare sex workers, those who can be charged are people who connect sex workers with users of sex workers, as well as people who facilitate prostitution. The next conclusion is that court decision Number 284/Pid.sus/2023/PN YKK is inappropriate in applying Article 296 of the Criminal Code to sex workers because the element of